Odpowiedź :
Odpowiedź:
a)
x - y = 2
2x + y = 13
x + 2x - y + y = 2 + 13
3x = 15 |:3
x = 5
x - y = 2 dla x = 5
5 - y = 2 |-5
-y = -3 |*(-1)
y = 3
x = 5
y = 3
b)
3x - 4y = 15
7x + 2y = 1 |*2
3x - 4y = 15
14x + 4y = 2
3x + 14x - 4y + 4y = 15 + 2
17x = 17 |:17
x = 1
3x - 4y = 15 dla x = 1
3*1 - 4y = 15
3 - 4y = 15 |-3
-4y = 12 \:(-4)
y = -3
x = 1
y = -3
c)
-2x + 3y = 5 |*3
6x - 8y = 3
-6x + 9y = 15
6x - 8y = 3
-6x + 6x + 9y - 8y = 15 + 3
y = 18
-2x + 3y = 5 dla y = 18
-2x + 3 * 18 = 5
-2x + 54 = 5 |-54
-2x = -49 |:(-2)
x = 24,5
x = 24,5
y = 18
d)
3x - 5y = 3,5 |*4
- 4x + 2y = -7 |*3
12x - 20y = 14
-12x + 6y = -21
12x - 12x - 20y + 6y = 14 - 21
-14y = -7 |:(-14)
y = 0,5
3x - 5y = 3,5 dla y = 0,5
3x - 5 * 0,5 = 3,5
3x - 2,5 = 3,5 |+2,5
3x = 6 |:3
x = 2
x = 2
y = 0,5
Szczegółowe wyjaśnienie: